Serum Paraoxonase-1 Activity and Paraoxonase Q192 Gene Polymorphism in a Young, Healthy Population - YAVUZ, DİLEK; ŞİRİKÇİ, ÖNDER; ÜSTAY, ÖZLEM; APAYDIN, TUĞÇE (TURKIYE KLINIKLERI, 2021)
Objective: Paraoxonase-1 (PON1) enzyme and PON Q192R gene polymorphism are associated with atherosclerosis in many middle-aged individuals and high populations at risk of cardiovascular disease. This study aimed to determine serum PON-1 and arylesterase (ARE) activities, PON Q192R polymorphism, and their association with gender, lipoprotein levels, and carotid intima-media thickness (CIMT) among young healthy individuals. Material and Methods: Four hundred fifteen healthy volunteers (F/M: 213/202, 19-25 years) were included in the study. Serum lipoprotein levels and PON1, ARE activities were measured using spectrophotometric methods. PON 192Q polymorphism was evaluated by polymerase chain reaction, and CIMT was measured using Doppler ultrasonography. Results: Serum PON1 activity and PON Q192R polymorphism frequencies were similar between men and women, while ARE activity was significantly higher in women. PON1 activity was considerably higher in RR carriers than in QQ and QR carriers among both men and women. Serum high-density lipoprotein level was lower, and CIMT was higher in men compared to women. Conclusion: PON1 enzyme activities did not differ according to gender, and ARE activity was higher in women. High PON1 activity is associated with PONQ192 RR polymorphism carriers. PON Q192 gene polymorphism could be a determinant of PON activity.
Keywords: Paraoxonase-1; paraoxonase Q192R gene; arylesterase; gender; high-HDL cholesterol; INTIMA-MEDIA THICKNESS; CORONARY-ARTERY-DISEASE; OXIDATIVE STRESS; PON1; RISK; LIPOPROTEINS; ASSOCIATION; PREDICTOR; PHENOTYPE; VARIABLES